Fast Implementation of the Rivest-Shamir-Adleman (RSA) Algorithm with Robust Packet Data Loss Detection Function - Mubasir, Issah; Abdul-Barik, Alhassan; Salamudeen, Alhassan (Asian Journal of Engineering and Applied Technology, 2021)
Encryption is the process of protecting information from unauthorized parties by converting such information into an unreadable form. Packet data is a method of transferring data, broken into bits called packets which travels over a network. Packet losses occur when packets fail to reach their destination devices as a result of network congestion, faulty routers or as a result of an attack. Encryption is the standard method for making a communication private. In sending a private message to another user, it is first encrypted (termed encipher), the intended recipient alone knows how to correctly decrypt (decipher) the message. There are several algorithms developed for the purpose of encryption which provides data security and integrity. This paper proposes the use of the Rivest-Shamir-Adleman (RSA) algorithm to implement a system for encrypting text files of any length (by breaking long messages into valid blocks and encrypting each block) capable of being transmitted using a Simple Mail Transfer Protocol (SMTP). Probable primes, 3048 bits in length are generated to be used in the generation of public, private key pairs for encryption and decryption. The proposed scheme is better because the route taken during transmission of data is recorded and packet losses are also checked for during transmission of encrypted files as compared to known state-of-the-art schemes.